Evaluation of musculoskeletal adverse effects in patients on systemic isotretinoin treatment: A cross-sectional study - Emine Müge Acar,; Senem Şaş,; Fatmanur Aybala Koçak, (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate the frequency of musculoskeletal adverse effects in acne vulgaris patients receiving systemic isotretinoin treatment. Patients and methods: Between January 2016 and December 2017, a total of 200 severe acne patients (22 males, 178 females; mean age: 21.8±0.4 years; range, 15 to 53 years) who were on isotretinoin treatment were retrospectively analyzed. Data including age, sex, body mass index (BMI), duration of disease, diagnosis, and comorbidities were recorded. Back pain severity was evaluated with the Visual Analog Scale (VAS). Results: The treatment period was mean 8.5±0.1 (range, 6 to 12) months. The dose of isotretinoin was mean 0.6±0.1 (range, 0.5 and 1) mg/kg. Musculoskeletal side effects were seen in 99 (49.5%) patients. Back pain was reported during the treatment period in 78 (78.7%) patients. The diagnosis was mechanical back pain in 31 (39.7%) and inflammatory back pain in 47 (60.3%) patients. The moderate-severe back pain group received higher cumulative isotretinoin doses than the mild back pain group (p=0.003). The BMI values did not show a significant difference between the patients with and without back pain (p=0.55). There was no significant correlation between the BMI and VAS scores (p=0.06). The VAS scores were found to be correlated with age (p=0.04). Sacroiliitis was diagnosed in four (4%) patients. One (1%) patient was diagnosed with enthesitis. Creatine kinase elevation was reported in 18 (18.1%) patients, while three (3%) patients described myalgia of mild severity. Conclusion: Low back pain is one of the most common musculoskeletal side effects of isotretinoin treatment that usually resolves with dose reduction. The cumulative dose of isotretinoin does not seem to play a role in the development of back pain, but can determine pain severity. Pain severity is directly correlated with the increasing age. Evaluation of the patients for musculoskeletal side effects during isotretinoin use is important in clinical practice, as it is a common occurrence.